The Effect Of Project Based Learning Model On Student’s Learning Results In Cognitive Domain and Creative Thinking Ability On Material Of Temperature and Calorie - Sitti Rahmi (USN Scientific Journal, 2023)
The aimed of this study were: 1) to determine the significant difference between the effect of project-based learning and direct learning model on students’ result of learning in cognitive domain, and 2) to find out the significant difference between the effect of project-based learning and direct learning model on students’ creative thinking ability before and after learning. Population of the study included all students of class VII at SMP Negeri 02 Rumbia. who enrolled in second semester of 2020/2021 academic year. Samples of the study were class VII.2 consisting of 25 students, as a control class, and class VII.5 consisting of 23 students as an eVIIperimental group. The result showed that: 1) there was a significant difference between the project-based learning model and the direct learning model in their effect on students’ results of learning in cognitive domain; and 2) there was a significant difference between the project-based learning model and the direct learning model in their effect on students’ creative thinking ability before and after learning. Thereby, project based learning had significant effect on students’ result of learning in cognitive domain and creative thinking ability before and after learning of temperature and calorie.